2018
DOI: 10.1016/j.nbd.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

D159 and S167 are protective residues in the prion protein from dog and horse, two prion-resistant animals

Abstract: Prion diseases are fatal neurodegenerative diseases caused by misfolding of the prion protein (PrP). These conditions affect humans and animals, including endemic forms in sheep and deer. Bovine, rodents, and many zoo mammals also developed prion diseases during the "mad-cow" epidemic in the 1980's. Interestingly, rabbits, horses, and dogs show unusual resistance to prion diseases, suggesting that specific sequence changes in the corresponding endogenous PrP prevents the accumulation of pathogenic conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 50 publications
2
59
0
Order By: Relevance
“…47 Furthermore, experiments with transgenic Drosophila expressing the D159N mutation (human equivalent of dogs 163) showed toxicity in contrast to WT dog PrP, concluding that D in position 159 was protective. 48 Our results with TgDog, together with previous reports on canine resistance to prion infection [32][33][34] clearly identify residue 163 as the strongest effector of the resistance of canine PrP C to misfolding. Therefore, to definitively demonstrate the importance of E or D in position 163, we substituted into the dog PrP the most conserved residue in susceptible species, asparagine, to determine if susceptibility of canine protein to misfolding could be induced.…”
Section: Discussionsupporting
confidence: 81%
“…47 Furthermore, experiments with transgenic Drosophila expressing the D159N mutation (human equivalent of dogs 163) showed toxicity in contrast to WT dog PrP, concluding that D in position 159 was protective. 48 Our results with TgDog, together with previous reports on canine resistance to prion infection [32][33][34] clearly identify residue 163 as the strongest effector of the resistance of canine PrP C to misfolding. Therefore, to definitively demonstrate the importance of E or D in position 163, we substituted into the dog PrP the most conserved residue in susceptible species, asparagine, to determine if susceptibility of canine protein to misfolding could be induced.…”
Section: Discussionsupporting
confidence: 81%
“…They revealed that salt bridges of the horse PrP can contribute to the maintenance of a stable molecular structure in a disordered environment by linking the structure of β2-sheet and α2-helix (Zhang, 2011). In addition, an amino acid alteration of the PRNP codon 167 from aspartic acid, which was conserved in various mammals, to serine, was only identified in horses and resulted in a well-defined structure of the β2-α2 loop, consequently presenting a noteworthy stability of the horse PrP (Perez et al, 2010;Sanchez-Garcia and Fernandez-Funez, 2018). Nevertheless, it is still proposed that further work should be conducted in horses.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the serine residue at codon 167 of the equine PrP, which is a horse-specific amino acid, contributes to the extraordinary stable structure of equine PrP and the resistance of prion disease [7]. Since a horse-specific amino acid showed distinct features in prion disease-resistant animals, we tried to find horse-specific amino acids in the Sho protein.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the stability of prion protein (PrP) and species-specific amino acids of PrP are related to prion disease susceptibility. The horse has a distinctive amino acid, S167, that contributes to the stability of horse PrP and non-toxicity in the transgenic Drosophila model [7]. In addition, the horse has four important salt bridges and a β2-α2 loop that contribute to the structural stability of horse PrP.…”
Section: Introductionmentioning
confidence: 99%